Looper: towards a methodology of co-design approaches. - Wiegmann, Mareille; Keserü, Imre; Macharis, Cathy (My University, 2018)
LOOPER (Learning Loops in the Public Realm) ist ein vom JPI Urban Europe Management Board finanziertes Forschungsprojekt mit Living Labs in Brüssel, Manchester und Verona. Ziel dieses Projekts ist der Aufbau einer partizipativen Co-Creation-Methodik und -Plattform zur Demonstration von "Lernschleifen", auf der Bürger, Interessengruppen und politische Entscheidungsträger iterativ lernen, wie städtische Herausforderungen (Straßenverkehrssicherheit, Verkehrsberuhigung, Luft- und Lärmbelastung) angegangen werden können.

When setting up their own participatory process, researchers and citizens alike are confronted with a wide array of online and offline tools targeted towards facilitating co-creation. With such a multitude of solutions available and approaches differing across countries and fields, how can one make an informed choice? This paper lays out the first results of a methods review that will create a co-creation and co-design toolbox for Living Labs. The review scopes across various disciplines and fields of application. Two promising physical toolkits and three comprehensive handbooks for facilitators are presented, detailing the circumstances under which they are potentially the most useful. The research takes place within LOOPER (Learning Loops in the Public Realm), a JPI Europe funded research project with Living Labs running in Brussels, Manchester and Verona. The aim of this project is to build a participatory co-creation methodology and platform to demonstrate "learning loops", bringing together citizens, stakeholders and policy-makers to iteratively learn how to address urban challenges (road safety, traffic calming, air and noise pollution). The review of existing tools serves as a preparatory activity for the Living Labs by developing the preliminary methodology which will form the backbone for the co-design of solutions in the living labs.
Keywords: Stadtentwicklungsplanung; Planungsprozess; Bürgerbeteiligung; Beteiligungsverfahren; Kommunikation; Kooperation; Reallabor